2007
DOI: 10.1603/0046-225x(2007)36[1475:ilbpfa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Improving Liquid Bait Programs for Argentine Ant Control: Bait Station Density

Abstract: Argentine ants, Linepithema humile (Mayr), have a positive effect on populations of mealybugs (Pseudococcus spp.) in California vineyards. Previous studies have shown reductions in both ant activity and mealybug numbers after liquid ant baits were deployed in vineyards at densities of 85-620 bait stations/ha. However, bait station densities may need to be <85 bait stations/ha before bait-based strategies for ant control are economically comparable to spray-based insecticide treatments-a condition that, if met,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 29 publications
0
56
1
Order By: Relevance
“…Ant control in vineyards has been investigated using granular protein baits for Formica species (Klotz et al 2003;Tollerup et al 2004) and liquid sugar baits for Argentine ants (Daane, Sime, et al 2006;Daane et al 2008;Nelson and Daane 2007 Klotz et al (2002) and described in detail by Daane, Sime, et al (2006).…”
Section: Developing Liquid Baitsmentioning
confidence: 99%
“…Ant control in vineyards has been investigated using granular protein baits for Formica species (Klotz et al 2003;Tollerup et al 2004) and liquid sugar baits for Argentine ants (Daane, Sime, et al 2006;Daane et al 2008;Nelson and Daane 2007 Klotz et al (2002) and described in detail by Daane, Sime, et al (2006).…”
Section: Developing Liquid Baitsmentioning
confidence: 99%
“…In such situations, infestation by Hemiptera is signiÞcantly reduced when the ants are excluded from the plants ). The control of L. humile in vineyards has been mainly carried out by applying insecticides on the ground or the trunks of the vines (Phillips and Sherk 1991, Addison 2002, Klotz et al 2003, Daane et al 2006, or with toxic baits (Nelson and Daane 2007, Daane et al 2008, Nyamukondiwa 2008, Blight et al 2011, Nyamukondiwa and Addison 2011. In these cases, the insecticides that are most often used as chemical barriers are chlorpyrifos, bifenthrin, and Þpronil (Phillips and Sherk 1991, Addison and Samways 2000, Klotz et al 2003, and as toxic baits are boric acid, Þpronil, hydramethylnon, imidacloprid, sulßuramid, and thiamethoxam (Klotz et al 1998;Rust 2000, 2001;Rust et al 2004;Nelson and Daane 2007;Daane et al 2008;Nyamukondiwa 2008;Nyamukondiwa and Addison 2011;Blight et al 2011).…”
mentioning
confidence: 99%
“…In this manner, L. humile can easily form supercolonies that can saturate an entire habitat. Nelson and Daane (2007) also found that L. humile is extremely vagile in Californian vineyards, whereas in citrus orchards Markin (1967Markin ( , 1968 and Ripa et al (1999) found that L. humile foraging seldom exceeds 61 m from a nest. Our research was limited to 32 m, as placing baits further apart would probably not result in effective control (see Daane et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…We presume that ants forage for shorter distances during this time of the year, since food resources will be highly abundant and in close proximity. Nelson and Daane (2007) hypothesized that ant foraging on 25% sugar water peaks in spring. Rust et al (2000) showed that L. humile foraged 26-60% and 16-40% of available protein in summer and winter respectively, suggesting considerable seasonal differences in activity and bait preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation